If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -2(-5x + -9) + 2x = 4(2x + -1) + -3(x + -12) Reorder the terms: 7 + -2(-9 + -5x) + 2x = 4(2x + -1) + -3(x + -12) 7 + (-9 * -2 + -5x * -2) + 2x = 4(2x + -1) + -3(x + -12) 7 + (18 + 10x) + 2x = 4(2x + -1) + -3(x + -12) Combine like terms: 7 + 18 = 25 25 + 10x + 2x = 4(2x + -1) + -3(x + -12) Combine like terms: 10x + 2x = 12x 25 + 12x = 4(2x + -1) + -3(x + -12) Reorder the terms: 25 + 12x = 4(-1 + 2x) + -3(x + -12) 25 + 12x = (-1 * 4 + 2x * 4) + -3(x + -12) 25 + 12x = (-4 + 8x) + -3(x + -12) Reorder the terms: 25 + 12x = -4 + 8x + -3(-12 + x) 25 + 12x = -4 + 8x + (-12 * -3 + x * -3) 25 + 12x = -4 + 8x + (36 + -3x) Reorder the terms: 25 + 12x = -4 + 36 + 8x + -3x Combine like terms: -4 + 36 = 32 25 + 12x = 32 + 8x + -3x Combine like terms: 8x + -3x = 5x 25 + 12x = 32 + 5x Solving 25 + 12x = 32 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 25 + 12x + -5x = 32 + 5x + -5x Combine like terms: 12x + -5x = 7x 25 + 7x = 32 + 5x + -5x Combine like terms: 5x + -5x = 0 25 + 7x = 32 + 0 25 + 7x = 32 Add '-25' to each side of the equation. 25 + -25 + 7x = 32 + -25 Combine like terms: 25 + -25 = 0 0 + 7x = 32 + -25 7x = 32 + -25 Combine like terms: 32 + -25 = 7 7x = 7 Divide each side by '7'. x = 1 Simplifying x = 1
| 7(6-3x)-3(8x+4)=30 | | 24+8x=80 | | r(x)=-2x^2-2x-5 | | 16X^2-24x-12=0 | | X/4=24.25 | | 3x-8=7x-60 | | 12t-8t=-25 | | (-3.5-x+1.7)+(9.1x-0.3)= | | 4[3p-5(p+2)]=19 | | -6(x-2)-(x-3)=(2x-8)-9 | | 8k-3+9=31 | | 5x-1+3x=-9 | | 8-1y=20 | | x^2y(x^3y-u)= | | 5x+18=7(x+3) | | -5(-3x-3)=5x-15 | | -27=x+9 | | txy=56 | | ln(x)+ln(x+29)=ln(62) | | X+6=-5x+30 | | -36t^2+18t=0 | | x^2y(xy-u)= | | -5(-3x-3x)=5x-15 | | 2154.28*.08= | | 2(n+8)=-18 | | x*0.07=150.80 | | X-(3-4)-1=5x-9-x | | 5x-5=6+6x | | 1/6m=20 | | (x+5)(-4x-2)(2x-1)=x | | 23n+10m+2n=180 | | 6m(m+4)=5m-15 |